Design, synthesis and biological evaluation of 4′-aminochalcone-rivastigmine hybrids as multifunctional agents for the treatment of Alzheimer's disease. Issue 3 (1st February 2017) - Xiao, Ganyuan; Li, Yan; Qiang, Xiaoming; Xu, Rui; Zheng, Yunxiaozhu; Cao, Zhongcheng; Luo, Li; Yang, Xia; Sang, Zhipei; Su, Fu; Deng, Yong
Graphical abstract: Abstract: A series of 4′-aminochalcone-revastigmine hybrids were designed, synthesized and evaluated as multifunctional agents for the treatment of Alzheimer's disease. The results showed that most of these compounds exhibited good multifunctional activities. In particular, compound6c displayed the best inhibitory potency on acetylcholinesterase (IC50 = 4.91 μM), and significant antioxidative activity with a value 2.83-fold of Trolox. The kinetic analysis of AChE inhibition revealed that6c showed mixed-type inhibition, binding simultaneously to the catalytic active site and peripheral anionic site of AChE. In addition, 6c inhibited self-induced A β 1-42 aggregation and Cu 2+ -induced A β 1-42 aggregation by 89.5% and 79.7% at 25 μM respectively, as well as acted as a selective monoamine oxidase B inhibitor (IC50 = 0.29 μM) and a selective biometal chelator. Furthermore, 6c could cross the blood-brain barrier in vitro . Based on these results, Compound6c could be considered as a very promising lead compound for Alzheimer's disease.